LEARNING ORGANIZATION DAN PENGARUHNYA TERHADAP KINERJA PEMERINTAH DESA: The Learning Organization and Its Impact on Village Government Performance - Okky Afriwan (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2026)
In the globalization most organization including village government organization must change tobe learning organizations. The aims of study is to analysis unflience of five components of learning organization to performance of village government. The study used associative method and hypotese is tested by regression linear model. The study result indicate that regression analysis outcome by F-test and t-test with ⍺0,05 level of significant is significance. It’s means that five learning organization influence to performance of village government.